1995
DOI: 10.1073/pnas.92.24.11019
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair in Escherichia coli enhances instability of (CTG)n triplet repeats from human hereditary diseases.

Abstract: Long CTG triplet repeats which are associated with several human hereditary neuromuscular disease genes are stabilized in ColEl-derived

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
134
4
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(145 citation statements)
references
References 23 publications
6
134
4
1
Order By: Relevance
“…For example, mismatch repair was found to be involved in CAG and CGG repeat instability E. coli (42). We and others have shown that intermolecular triplexes are recognized by the nucleotide excision repair (NER) factors XPA and RPA, followed by an error-prone repair resulting in site-specific mutagenesis, both in cells and in animals (19,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mismatch repair was found to be involved in CAG and CGG repeat instability E. coli (42). We and others have shown that intermolecular triplexes are recognized by the nucleotide excision repair (NER) factors XPA and RPA, followed by an error-prone repair resulting in site-specific mutagenesis, both in cells and in animals (19,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Long CTG repeats are stabilized in ColE1-derived plasmids in E. coli containing mutations in the methyl-directed mismatch repair genes (mutS, mutL, or mutH) (34). When plasmids containing (CTG) 180 were grown for about 100 generations in mutS, mutL, or mutH strains, 60 -85% of the plasmids contained a full-length repeat, whereas in the parent strain only about 20% of the plasmids contained the full-length repeat.…”
Section: Mismatch Repairmentioning
confidence: 99%
“…However, our data suggest that, once formed, ordered, single-stranded triplet repeat structures can represent local minima. Errors in the passage of the replication fork through the triplet repeat domain (10,67,68), faulty repair processes (69,70), or some other yet-to-be-determined mechanism may lead to expansion of triplet repeat DNA when such single-stranded ordered states are populated. Because the onset of the expansion of the triplet repeat domain may depend on such metastable states, the lifetime as well as the relative thermodynamic stability of the ordered structure must be considered in the regulation of events that allow expansion to occur.…”
Section: Biological Implicationsmentioning
confidence: 99%